Campaign rhetoric and the hide-and-seek game - Bhattacharya, Sourav (Social choice and welfare, 2016)
We present a model of political campaigning where a candidate chooses between promoting oneself (positive campaign) or attacking the rival (negative campaign). Candidates vary only by quality. Campaign choices determine the subject of public deliberation: If a candidate runs a positive campaign and his rival a negative campaign, the voters learn the quality of the "focal" candidate. Thus, negative campaigns may be used either to expose the rival candidate (informative role) or to turn attention away from oneself (non-informative role). The effect of negative campaigns depends on whether it is faced with another negative campaign (cross talk) or a positive campaign (fruitful debate). We suggest that in order to ascertain the effect of negative advertising, studies should take into account the campaigns employed by both candidates. Voter beliefs about candidate quality plays a major role in campaign selection: while the incidence of negative campaigning goes down as the prior probability of a candidate being good increases, the probability of selection of the correct candidate is non-monotonic in the said prior.